Indikator, Prospek dan Cabaran Masjid dalam Membangunkan Modal Insan Berintegriti: Satu Kajian Kes di Negeri Johor: Indicators, Prospects and Challenges Faced by Mosque in Developing Integrity-Based Human Capital: A Case Study in Johore - Sohar, Fadzil; Md Ariffin, Mohd Farhan; Mohd Rokhibi, Ibrahim Adham (Al-Basirah Journal, 2024)
This study aims to analyze the indicators, prospects and challenges faced by the Johor State Mosque in an effort to develop human capital with integrity. The mosque as an important institution in the Islamic community plays a significant role in the formation of moral values ​​and individual integrity. This case study uses a qualitative approach with in-depth interviews and document analysis to obtain relevant data. The results of the study found that the Johor State Mosque has implemented various programs such as religious talks, Quran study classes and community activities that aim to strengthen the value of integrity in the community. However, there are several key challenges identified, including lack of financial resources, lack of involvement of the younger generation and mosque leadership issues. Despite this, this study also identified positive prospects such as support from the state government and potential strategic collaboration with educational institutions and non-governmental organizations. This study suggests that a more inclusive and innovative approach be applied to ensure the effectiveness of human capital development programs with integrity in mosques. The implications of this study provide guidance to mosque management and stakeholders in strengthening the institutional role of the mosque as an agent of social change.